Essentials of Spinal Stabilization - Holly, Langston T.; Anderson, Paul A. (Springer International Publishing : Imprint: Springer, 2017)
This text includes stabilization techniques for the entire spinal column, ranging from the cranio-cervical junction to the pelvis. The information is presented in an easily digestible format that is suitable for those in school or training, yet includes pearls and insight that can be appreciated by even the most seasoned surgeon. The text is divided into major sections based on the anatomical regions of the spine - cervical, thoracic, and lumbosacral. An additional section is devoted to related surgical concepts and principles such as spinal biomechanics, computer image guidance, and deformity surgery. Each chapter has a uniform design including background, indications, patient selection, preoperative considerations, surgical technique, technical pearls, and strategies for complication avoidance. Preoperative and postoperative images and/or illustrations are utilized to highlight the presented information. Edited by a Neurosurgeon and an Orthope dist and written by leading national and international Neurosurgery and Orthopedic spine experts, Essentials of Spinal Stabilization provides a text which will broadly appeal to all spine care professionals.
Keywords: Medicine.; Neurosurgery.; elektronické knihy; electronic books